2008
DOI: 10.1097/gco.0b013e3282f4ef9e
|View full text |Cite
|
Sign up to set email alerts
|

Timing of injury in the fetus and neonate

Abstract: There is now strong evidence that brain injury commonly occurs in the immediate perinatal period, and so may be potentially treatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Recent clinical trials have demonstrated that the incidence of death and disability from hypoxia-ischemia in newborns can be significantly reduced by initiating treatment strategies, hypothermia, for example, after birth and within a 6-h therapeutic window (9,11,14,32). Due to the brevity of the therapeutic window, early detection of injury and early determination of those infants who are likely candidates for treatment are crucial (15). In this regard, traditional early indicators of brain injury, including Apgar scores, umbilical artery acidosis, and fetal heart rate monitoring, suffer from poor specificity (7,31), and more specific indicators of injury, such as magnetic resonance imaging and spectroscopy, are insensitive or difficult to implement within the therapeutic window (6,21).…”
mentioning
confidence: 99%
“…Recent clinical trials have demonstrated that the incidence of death and disability from hypoxia-ischemia in newborns can be significantly reduced by initiating treatment strategies, hypothermia, for example, after birth and within a 6-h therapeutic window (9,11,14,32). Due to the brevity of the therapeutic window, early detection of injury and early determination of those infants who are likely candidates for treatment are crucial (15). In this regard, traditional early indicators of brain injury, including Apgar scores, umbilical artery acidosis, and fetal heart rate monitoring, suffer from poor specificity (7,31), and more specific indicators of injury, such as magnetic resonance imaging and spectroscopy, are insensitive or difficult to implement within the therapeutic window (6,21).…”
mentioning
confidence: 99%
“…The current study thus found an association between perinatal oxygen perfusion problems and DCD, as we found previously on a larger study using questionnaire data only (Pearsall-Jones et al, 2008). In our studies it was not clear whether movement difficulties in these twins resulted from perinatal oxygen perfusion problems, or whether, as proposed by Gunn and Bennet (2008), exposure to infections in utero cumulatively sensitized them to hypoxia at birth, or because of prenatal cardiac or lung problems leading to perinatal oxygen perfusion problems (Morley, 2005). In neonatal hypoxic-ischemic encephalopathy, 20-30% of survivors were estimated to have long term neurodevelopmental sequelae, including CP (Vannucci & Perlman, 1997).…”
Section: Twin Research and Human Genetics August 2009mentioning
confidence: 69%
“…Timing of exposure to infections is important, and may have long-term cumulative effects; for example, increased sensitization to hypoxia at birth and in later life (Gunn & Bennet, 2008). Discordant outcome may also be a result of birth complications and presentation (Bjelic-Radisic et al, 2007) and birth order (Hartley & Hitti, 2005;Smith et al, 2007).…”
mentioning
confidence: 99%
“…Due to the brevity of the therapeutic window, early detection of injury and an early determination of those infants who are likely candidates for treatment are crucial (Gunn & Bennet, 2008). In this regard, traditional early indicators of brain injury -including Apgar scores, umbilical artery acidosis and fetal heart rate monitoring -suffer from poor specificity (Carter et al, 1998;Shankaran, 1998) and more specific indicators of injury, such as magnetic resonance imaging and spectroscopy, are insensitive or difficult to implement within the therapeutic window (Cady, 2001;Martin & Barkovich, 1995).…”
Section: Detection Of Hypoxia-ischemiamentioning
confidence: 99%